Existentialism and the Search for Meaning in Contemporary Philosophy - Rifki Zaitul Ikhlas; Omar Khan; Amir Raza (Yayasan Adra Karima Hubbi, 2024)
Background. Existentialism as a school of philosophy that emphasizes personal freedom and responsibility continues to be relevant in the context of contemporary life, where individuals are increasingly feeling social pressures and identity crises. Purpose. This research aims to explore how existentialism can help individuals in their search for meaning in life amid modern complexity and uncertainty. Method. Using qualitative research methods with a phenomenological approach, this study involved in-depth interviews with adult individuals aged 25-50 years who have an interest in existentialist philosophy. Results. The results of the study show that existentialism is not only an abstract philosophical view, but also serves as a practical guide in daily life. Most participants stated that existentialism helped them deal with existential crises, social pressures, and life uncertainties through deep self-reflection and an emphasis on freedom and responsibility. Conclusion. The conclusion of this study indicates that existentialism can make a practical contribution in helping individuals find authentic meaning in life. This study recommends further research on the application of existentialism in various cultural and social contexts to deepen the understanding of the relevance of this philosophy in the modern era.